2019
DOI: 10.3310/hta23500
|View full text |Cite
|
Sign up to set email alerts
|

A bespoke smoking cessation service compared with treatment as usual for people with severe mental ill health: the SCIMITAR+ RCT

Abstract: Background There is a high prevalence of smoking among people with severe mental ill health (SMI). Helping people with SMI to quit smoking could improve their health and longevity, and reduce health inequalities. However, those with SMI are less likely to access and engage with routine smoking cessation services than the general population. Objectives To compare the clinical effectiveness and cost-effectiveness of a bespoke s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…We define SMI as any mental illness that causes significant functional impairment and substantially limits major life activities. 20 This definition is consistent with the RCT populations for the BSCI which included people with schizophrenia, psychotic illness, and bipolar disorder 19 ; and IC where the included population had clinical-administered PTSD scale (CAPS) scores indicative of severe PTSD. 13 Our population was also limited to people aged 12 to 100 as this represented the youngest and oldest ages for which smoking related prevalence data were available.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…We define SMI as any mental illness that causes significant functional impairment and substantially limits major life activities. 20 This definition is consistent with the RCT populations for the BSCI which included people with schizophrenia, psychotic illness, and bipolar disorder 19 ; and IC where the included population had clinical-administered PTSD scale (CAPS) scores indicative of severe PTSD. 13 Our population was also limited to people aged 12 to 100 as this represented the youngest and oldest ages for which smoking related prevalence data were available.…”
Section: Methodsmentioning
confidence: 90%
“…The comparator, usual care, was standard NHS stop smoking services which could include pharmacological and behavioural support, but this was not tailored to individual need. 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies set out to explore the cost-effectiveness of the intervention. The SCIMITAR study (2015) [32] was a pilot study that was not sufficiently powered for any firm conclusions to be drawn; however, in Peckham et al (2019) [38] and Li (2020) [39] (who report the cost-effectiveness of the SCIMITAR intervention [14]) it was demonstrated that a smoking cessation intervention, tailored to the needs of people with SMI, was cost-effective over 12 months. The mean total cost in the intervention group was £270 (95% = −£1690 to 1424) lower than in the usual care group, while the mean QALYs were 0.013 (95% CI = −0.008 to 0.045) higher, leading to smoking cessation dominating usual care (76% probability of cost-effective at £20 000/ QALYs).…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…We conducted a 12‐month pragmatic two‐arm parallel group individually randomized controlled trial (RCT) to compare a bespoke smoking cessation (BSC) intervention ( n = 265) with usual care (UC) ( n = 261) (SCIMITAR+ trial). The report of the project has been published in full in health technology assessment [8]. The protocol has been published previously [9].…”
Section: Introductionmentioning
confidence: 99%